Meningkatkan Kemampuan Berpikir Kritis dan Kemandirian dengan Menggunakan Model PBL pada Materi Memperjuangkan Nilai-Nilai Kehidupan untuk Kelas XII IPA SMA Pax Patriae Tahun Ajaran 2024/2025 - Elfridus Moi; Anselmus Yata Mones; Maria Margaretha Dwilinda (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
This Classroom Action Research (CAR) aims to improve the critical thinking skills and independence of 12th-grade students in Catholic Religious Education through the application of the Problem-Based Learning (PBL) model on the topic of advocating life values in society. Critical thinking skills and independence are essential for students to face the challenges of modern life and build a deeper understanding of the values from Scripture and the Catholic Church's teachings. The study was conducted in two cycles, where each cycle consisted of planning, implementation, observation, and reflection. The research was conducted on 23 12th grade students. Observation sheets, critical thinking, and independence tests were among the instruments used. The study's findings indicate that the PBL model significantly improves students' critical thinking and independence. Cycle I saw a moderate improvement, but Cycle II saw a significant increase in students' critical thinking and independence following adjustments. Students were able to connect the values of Scripture and Church teachings with real-life contexts and became more independent in completing assigned tasks. Thus, the Problem-Based Learning model is highly effective in enhancing students' critical thinking and independence in the topic of life values in society within Catholic Religious Education. The implementation of PBL can continue to be developed to improve the quality of learning and students' life skills.